2020
DOI: 10.7717/peerj.9972
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infection after cardiac surgery: Assessment of prevalence, risk factors and clinical outcomes—retrospective study

Abstract: Background Clostridioides difficile infection (CDI) is the most common cause of hospital-acquired diarrhea. There is little available data regarding risk factors of CDI for patients who undergo cardiac surgery. The study evaluated the course of CDI in patients after cardiac surgery. Methods Of 6,198 patients studied, 70 (1.1%) developed CDI. The control group consisted of 73 patients in whom CDI was excluded. Perioperative data and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These may include host factors (immune status, comorbidities), exposure to CD spores (hospitalizations) and other factors that disrupt normal colonic microbiome (antibiotics and other medications or surgery) [ 6 ]. It has also been shown that high glucose levels and stress hyperglycemia during the early postoperative period were associated with greater risk for development of CDI in patients following cardiac surgery [ 7 ]. It is unclear whether other acid-base disturbances, especially the development of hyperlactatemia in the perioperative period, may impact CDI occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…These may include host factors (immune status, comorbidities), exposure to CD spores (hospitalizations) and other factors that disrupt normal colonic microbiome (antibiotics and other medications or surgery) [ 6 ]. It has also been shown that high glucose levels and stress hyperglycemia during the early postoperative period were associated with greater risk for development of CDI in patients following cardiac surgery [ 7 ]. It is unclear whether other acid-base disturbances, especially the development of hyperlactatemia in the perioperative period, may impact CDI occurrence.…”
Section: Introductionmentioning
confidence: 99%